Nurse-related behavioural determinants associated with healthy eating support provided by Dutch community nurses: a cross-sectional study - Gerlinde Den Hamer-Jordaan; Geertruida J. Groenendijk-van Woudenbergh; Willemieke Kroeze; Ellemijn Troost; Annemien Haveman-Nies (BMC, 2024)
Abstract Background Community nurses (CNs) play an important role in supporting healthy lifestyles, including healthy eating behaviour of patients. However, many CNs do not incorporate healthy eating support in their daily routines to the fullest extent possible. This study aimed to explore (1) the associations between nurse-related behavioural determinants and self-reported healthy eating support practices of Dutch CNs and (2) CNs' need for additional knowledge. Methods In this cross-sectional survey design, 244 Dutch CNs completed an online, self-administered questionnaire in October-November 2021. The 60 questionnaire items were related to CNs' characteristics, nurse-related determinants, healthy eating support practices (observing problems, having a conversation about patients' dietary behaviour, motivating patients to eat and drink healthier and supporting patients in goal setting) and the need for additional knowledge. The items on determinants and practices used a 5-point Likert scale. Adjusted prevalence ratios (PRadjusted) with 95% confidence intervals (95%CIs) were obtained for the associations between determinants and practices, using adjusted Poisson regression with robust variance estimations. Results More CNs practiced observing problems (75%) and having a conversation (70%) than did motivating patients (45%) and supporting goal setting (28%) at least often. A more positive attitude (PRadjusted 1.8; 95%CI 1.5-2.2), greater self-efficacy (PRadjusted 1.3; 95%CI 1.1-1.5), greater motivation (PRadjusted 1.5; 95%CI 1.3-1.7) and better abilities (PRadjusted 1.4; 95%CI 1.2-1.6) were associated with a greater prevalence of supporting healthy eating at least often (vs. never to sometimes). Barriers were not associated with healthy eating support (PRadjusted 1.1; 95%CI 1.0-1.2). CNs especially desired more knowledge on diet in relation to cancer, gastrointestinal diseases, severe psychiatric diseases and dementia; methods for motivating patients to start and for supporting patients to sustain healthy eating; and dealing with patient autonomy. Conclusions This study suggests that nurse-related behavioural determinants such as attitude, self-efficacy, motivation and ability should be addressed to improve CNs' competences in healthy eating support. In addition, based on self-reported need for additional knowledge, it is recommended to pay attention to evidence-based behaviour change techniques, dealing with patient autonomy, and diet in relation to cancer, gastrointestinal diseases, severe psychiatric diseases and dementia. Reporting method The STROBE Statement was followed for reporting.